Reactive organic matter destabilizes Fe-mediated phosphorus retention through Fe–S–P decoupling in lake sediments - Yaping Liu; Lixin Jiao; Jia He; Liansheng He; Di Song; Jing Liu; Yaru Feng (Water Research, 2026)

Orbital-hybridized electron bridge enables functional compartmentalization for ultradeep electrosorption - Bijie Bie; Xiaodong Xie; Shuncai Luo; Qingtan Xu; Song Xie; Yaping Miao; Xuming Zhang; Biao Gao; Zhaobo Wang; Buxiao Kuang; Fang Zhou; Liwei Xiong; et al. (Chemical Engineering Journal, 2026)

Optimizing Holstein bovine oocyte development: Evidence-Based donor selection for OPU-IVP - Heqiang Li; Baobao Zhao; Jingya Wang; Xuexiao Song; Jieyu Wang; Yang Li; Zihan Xu; Zheng Wang; Yaochang Wei; Zhuangsheng Wang; Yaping Jin; Yongsheng Wang (Theriogenology, 2026)

The exosomal bta-miR-1246/ATOH8 signaling axis: A key Regulator of intramuscular adipocytes development and beef marbling - Yaping Song; Dongmei Yang; Chao Jiang; Xiaoyu Song; Ruopu Jiao; Hongfang Gong; Yilun Ma; Sayed Haidar Abbas Raza; Sameer Dinkar Pant; Guijie Zhang; Yun Ma; Linsen Zan; et al. (Food Bioscience, 2026)

Rapid particulate microplastics removal from stormwater: Distinct adsorption behavior and data-driven intelligent prediction - Yan Yaping; Song Xichen; Wang Xiaojuan; Liu Xiuyun; Zhou Jianqiang; Wang Gang; Zhang Tingting; Wei Bigui; Zhao Yaqian (Chemical Engineering Journal, 2026)

Wettability-switchable deep bed filtration for efficient oily wastewater treatment - Song Xichen; Yan Yaping; Zhang Tingting; Zhou Jianqiang; Wang Xiaojuan; Wang Zhezhe; Lin Jialong; Wang Ting; Song Xiaosan; Dai Liang; Wang Gang; Gao Suxia; et al. (Journal of Hazardous Materials, 2026)

Exploring contributions and responses of microbial quantity and diversity to coastal seasonal hypoxia - Guihao Li; Jiarong Hu; Pengfei Zheng; Ping Zhu; Yaping Wang; Songbao Zou; Xiaoli Zhang; Eleni Gentekaki; Song Sun; Aolin Zhu; Jun Gong (Marine Pollution Bulletin, 2026)

Design, synthesis, and biological evaluation of glycyrrhetinic acid–cinnamamide derivatives as HMGB1/TLR4 pathway inhibitors for sepsis-induced liver injury - Jiao Wang; Tian Guo; Zhe Zheng; Yaping Zhang; Zhian Zha; Xiaohan Zhang; Jie Song; Dongyi Wei; Jianbin Yang (Molecular Diversity, 2026)

Coordinative interlocking stabilizes MOFs for enhanced structural and antibacterial performance - Jiayuan Wang; Yaping Zhang; Tingyao Li; Kai Wang; Rongmin Wang; Yufeng He; Pengfei Song (Chemical Engineering Journal, 2026)

Corrigendum to “Busulfan plus cyclophosphamide induced spermatogenic dysfunction and recovery: A dynamic change perspective” [Toxicol. Lett. 417(2026) 111833] - Tianyu Li; Zhichen Tang; Yaping Song; Min Su; Xiao Liu; Fuping Li; Xing Wei; Xiaolei Luo; Bin Zhou; Yanyun Wang; Lin Zhang (Toxicology Letters, 2026)

Analysis of WNT5A as a key regulator of intramuscular fat deposition in muscle-adipocyte co-cultures - Hongfang Gong; Yaping Song; Dongmei Yang; Chao Jiang; Ruopu Jiao; Yilun Ma; Sayed Haidar Abbas Raza; Jiupan Zhang; Dawei Wei (Tissue and Cell, 2026)

Removal performance and mechanisms of microplastics by superhydrophobic medium - Zhang Tingting; Cheng Wenqing; Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Gao Suxia; Li Hao; Liu Jianlin; Cao Lianbao; Li Wei; et al. (Journal of Environmental Chemical Engineering, 2026)

Busulfan plus cyclophosphamide induced spermatogenic dysfunction and recovery: A dynamic change perspective - Tianyu Li; Zhichen Tang; Yaping Song; Min Su; Xiao Liu; Fuping Li; Xing Wei; Xiaolei Luo; Bin Zhou; Yanyun Wang; Lin Zhang (Toxicology Letters, 2026)

Study on the removal and ecological risk of microplastics in road runoff by collapsible loess bioretention facilities - Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Zhang Tingting; Gao Suxia; Li Jiapeng; Liu Jianlin; Cao Lianbao; Li Wei; Wei Bigui (Process Safety and Environmental Protection, 2026)

Synthesis of borneol-based cationic copolymer microspheres via a dual strategy of stereochemistry and cationic sterilization for antibacterial coatings - Xiaobing Ma; Xiangbin Sun; Yuanyuan Xie; Rongmin Wang; Yaping Zhang; Yufeng He; Pengfei Song (Journal of Environmental Chemical Engineering, 2026)

Resveratrol can inhibit porcine reproductive and respiratory syndrome virus infection in vitro and in vivo by inhibiting PI3K/Akt signaling pathway - Yaping Chen; Wenshuang Chen; Xinqi Song; Xinyi Zhao; Li Yang; Ruoyu Zhao; Meilong Song; Bingbing Zhang; Dongbo Sun (Veterinary Microbiology, 2026)

Local actors and urban green development in China's energy-rich regions: a case study of the Shanxi-Shaanxi-Inner Mongolia region - Binkai Zheng; Yongyong Song; Yaping Wang; Siyou Xia; Xiping Yang; Beibei Ma; Dongqian Xue (Applied Geography, 2026)

Multi-Omics analysis unveils the regulatory mechanism of ZNF423 in bovine intramuscular fat formation - Xiaoyu Song; Jiupan Zhang; Yaping Song; Sayed Haidar Abbas Raza; Sameer Dinkar Pant; Linsen Zan; Guijie Zhang; Dawei Wei (Functional & Integrative Genomics, 2025)

Phosphoenolpyruvate carboxykinase 2 (PCK2) attenuates bovine adipocyte lipolysis through PNPLA2 activity repression - Chao Jiang; Hao Wu; Jiupan Zhang; Yaping Song; Xiaoyu Song; Ruopu Jiao; Sayed Haidar Abbas Raza; Sameer Dinkar Pant; Linsen Zan; Dawei Wei (Functional & Integrative Genomics, 2025)

Corrigendum to “Lysosomal signaling in adipogenesis regulation: A novel pathway to enhance marbled beef quality” [Food Bioscience 68 (2025) 106447] - Xiaoyu Song; Jiupan Zhang; Yaping Song; Chao Jiang; Sayed Haidar Abbas Raza; Sameer Dinkar Pant; Yun Ma; Yanfen Ma; Guijie Zhang; Linsen Zan; Dawei Wei (Food Bioscience, 2025)

Transcriptional repression of CYP26B1 by EBF2 activates retinol metabolic pathway: A strategy to enhance lipid storage and marbling potential of beef - Yaping Song; Chenglei Song; Jiupan Zhang; Dongmei Yang; Chao Jiang; Ruopu Jiao; Hongfang Gong; Yilun Ma; Sayed Haidar Abbas Raza; Sameer Dinkar Pant; Yun Ma; Guijie Zhang; et al. (Food Bioscience, 2025)

Environmental tobacco smoke exposure in pregnant women and thyroid hormone levels in newborn cord blood: A birth cohort in China - Tengwei Gui; Yan Li; Yaping Liu; Jirong Li; Tong Luo; Shuqi Chen; Xiaoxiao Song; Xia Xiao (Environmental Pollution, 2025)

Lysosomal signaling in adipogenesis regulation: A novel pathway to enhance marbled beef quality - Xiaoyu Song; Jiupan Zhang; Yaping Song; Chao Jiang; Sayed Haidar Abbas Raza; Sameer Dinkar Pant; Yun Ma; Yanfen Ma; Guijie Zhang; Linsen Zan; Dawei Wei (Food Bioscience, 2025)

Associations Between Organophosphate Esters Exposure and Metabolic Syndrome: Exploring the Mediating Role of Oxidative Stress and Inflammation in Adults - Sijie Yang; Yaping Li; Ling Liu; Zhengce Wan; Qitong Xu; Chang Xie; Lulu Song; Youjie Wang; Hui Chen; Surong Mei (Exposure and Health, 2025)

A lightweight prediction model for global ionospheric total electron content based on attention-BiLSTM - Chao Han; Yaping Guo; Ming Ou; Dandan Wang; Chenglong Song; Ruimin Jin; Weimin Zhen; Peirui Bai; Xiaorui Chong; Xiaoni Wang (Advances in Space Research, 2025)

Gold nanoparticle-catalyzed oxidative esterification of furfural: Enhancement by NaOH-etched γ-Al2O3 support - Xianjie Li; Bingxiao Feng; Hailin Zhang; Yaping Liu; Meng Xiao; Tingting Huang; Quanhong Zhu; Hongbing Song (Fuel, 2025)

Rice rhizosphere microbiome is more diverse but less variable along environmental gradients compared to bulk soil - Yaping Guo; Yakov Kuzyakov; Na Li; Bin Song; Zihao Liu; Jonathan M. Adams; Lin Yang (Plant and Soil, 2025)

Multi-omics integration analysis reveals metabolic regulation of carbohydrate and secondary metabolites during goji berry (Lycium barbarum L.) maturation - Yaping Ma; Mura Jyostna Devi; Lihua Song; Handong Gao; Lei Jin; Bing Cao (Postharvest Biology and Technology, 2024)

Influence of dissolved and non-aqueous phase toluene on spectral induced polarization signatures of soils - Yalin Song; Xiaoqing Shi; André Revil; Yaping Deng (Journal of Hazardous Materials, 2024)

The association of organochlorine pesticides and polychlorinated biphenyls exposure with dyslipidemia and blood lipids: The mediating effect of white blood cell counts - Mingye Zhang; Lipan Wang; Xiang Li; Limei Wang; Yaping Li; Sijie Yang; Lulu Song; Zhengce Wan; Yongman Lv; Youjie Wang; Surong Mei (Environmental Pollution, 2024)

Effects of LAZY family genes on shoot gravitropism in Lotus japonicus - Shaoming Xu; Shusi Song; Huawu Jiang; Guojiang Wu; Yaping Chen (Plant Science, 2024)

Different contributions of meteorological conditions and emission reductions to the ozone pollution during Shanghai’s COVID-19 lockdowns in winter and spring - Xuedan Dou; Mengying Li; Yaping Jiang; Zhe Song; Pengfei Li; Shaocai Yu (Atmospheric Pollution Research, 2024)

Effect of maternal cigarette smoke exposure on COPD progression in offspring mice - Jiawei Sun; Huan Chen; Xu Xu; Yaping Dou; Baofa Wu; Hongyang Zhang; Song Shang; Wuzhuang Sun (Reproductive Toxicology, 2024)

Thiophene-containing conjugated polymers modified Zn0.5Cd0.5S inorganic/organic S-scheme heterojunction for boosting photocatalytic hydrogen production coupled with benzyl alcohol oxidation - Lele Wei; Ru Song; Jiarui Song; Yaping Li; Yina Nie; Lin Liu; Jun Wan (Chemical Engineering Journal, 2024)

Individual and joint effects of organophosphate esters and hypertension or diabetes on renal injury among Chinese adults - Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Chang Xie; Zhengce Wan; Lulu Song; Yongman Lv; Youjie Wang; Hui Chen; Surong Mei (International Journal of Hygiene and Environmental Health, 2024)

Low-humidity sensor and biomimetic power supply based on mesoporous silica/polymerizable deep eutectic solvent ionogels - Zhiyan Ma; Yanyu Cui; Yaping Song; Yunlong Yu; Hongran Zhao; Sen Liu; Xishuang Liang; Teng Fei; Tong Zhang (Chemical Engineering Journal, 2024)

Association between organophosphate esters individual and mixed exposure with the risk of hyperlipidemia and serum lipid levels among adults in Wuhan, China - Qitong Xu; Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Zhengce Wan; Lulu Song; Yongman Lv; Hui Chen; Youjie Wang; Surong Mei (Environmental Science and Pollution Research, 2024)

Associations of exposure to organochlorine pesticides and polychlorinated biphenyls with chronic kidney disease among adults: the modifying effects of lifestyle - Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Zhengce Wan; Lulu Song; Yongman Lv; Dan Luo; Qiang Li; Youjie Wang; Hui Chen; et al. (Environmental Science and Pollution Research, 2024)

Efficient separation of cresol isomers using azeotropic coupling pressure-swing distillation: From separation mechanism to process integration - Chao Pan; Jingtao Guo; Yaping Liu; Bingxiao Feng; Guoxuan Li; Hengjun Gai; Hongbing Song; Meng Xiao; Tingting Huang; Quanhong Zhu (Fuel, 2024)

Oxidative esterification of 5-hydroxymethylfurfural to dimethyl 2,5-furandicarboxylate over Au-supported poly(ionic liquid)s - Yaping Liu; Chao Pan; Xiaomin Qiu; Xianjie Li; Hengjun Gai; Meng Xiao; Tingting Huang; Quanhong Zhu; Hongbing Song (Fuel, 2024)

Distinct biogeographic patterns in Glomeromycotinian and Mucoromycotinian arbuscular mycorrhizal fungi across China: A meta-analysis - Zihao Liu; Jie Fang; Yucheng He; Gary D. Bending; Bin Song; Yaping Guo; Xiaojie Wang; Zemin Fang; Jonathan M. Adams (Science of The Total Environment, 2024)

Large contributions of emission reductions and meteorological conditions to the abatement of PM2.5 in Beijing during the 24th Winter Olympic Games in 2022 - Yaping Jiang; Shaocai Yu; Xue Chen; Yibo Zhang; Mengying Li; Zhen Li; Zhe Song; Pengfei Li; Xiaoye Zhang; Eric Lichtfouse; Daniel Rosenfeld (Journal of Environmental Sciences, 2024)

An assessment of natural and anthropogenic influences on atmospheric fluoride deposition in central Tibetan Plateau during 1951–2008 A.D. using the Zangser Kangri ice core - Xiang Zou; Wangbin Zhang; Shuangye Wu; Jinhai Yu; Jing Song; Hongxi Pang; Yaping Liu; Shugui Hou (Atmospheric Environment, 2024)

Micro-mechanism of the effect of multi-component gas injection on methane recovery - Huan Zhang; Wenfei Tao; Xiangyang Zhang; Hongbao Zhao; Shuangli Du; Chuang Song; Yaping lv; Haonan Chai; Mingyi Wang (Journal of Environmental Chemical Engineering, 2023)

Synergistic catalytic wet oxidation of ammonia over carbon-supported low-loading Ru/Cu bimetallic catalyst - Donglin Yang; Bingxiao Feng; Yaping Liu; Chaoting Deng; Hengjun Gai; Meng Xiao; Tingting Huang; Quanhong Zhu; Hongbing Song (Journal of Environmental Chemical Engineering, 2023)

Simple and efficient strategy for α-MnO2/C by in-situ synthesis and its performance for degrading urea process wastewater - Yanli He; Shuguang Shen; Ying Wang; Chenyuan Guo; Yaping Yuan; Yaru Fan; Lili Zhang; Yuyan Song (Journal of Environmental Chemical Engineering, 2023)

Putrescine (1,4-Diaminobutane) enhances antifungal activity in postharvest mango fruit against Colletotrichum gloeosporioides through direct fungicidal and induced resistance mechanisms - Yaping Song; Yanfang Ren; Yuhao Xue; Dandan Lu; Tengyu Yan; Junyu He (Pesticide Biochemistry and Physiology, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

Au loaded mesoporous SiO2/gelatin hydrogel: Detecting low humidity and NH3 - Zhiyan Ma; Yunlong Yu; Ke Wu; Yaping Song; Sen Liu; Xi Yang; Teng Fei; Tong Zhang (Chemical Engineering Journal, 2023)

Construction of hexagonal spindle-shaped Fe-MOFs induced by cationic copolymer and its application for effective wastewater treatment - Yaping Zhang; Duoxin Zhang; Yufeng He; Zeyuan Wang; Pengfei Song; Rongmin Wang (Environmental Science and Pollution Research, 2023)

Uncovering the dynamic evolution of microbes and n-alkanes: Insights from the Kuroshio Extension in the Northwest Pacific Ocean - Xin Hu; Xinping Wang; Shanshan Zhao; Lixin Cao; Yaping Pan; Fujuan Li; Fengshu Li; Jinren Lu; Yiming Li; Guodong Song; Honghai Zhang; Peiyan Sun; et al. (Science of The Total Environment, 2023)

Coordination number engineering of Zn single-atom sites for enhanced transfer hydrogenation performance - Yaping Song; Rou Guo; Binbin Feng; Yanghe Fu; Fumin Zhang; Yifei Zhang; De-Li Chen; Jiangwei Zhang; Weidong Zhu (Chemical Engineering Journal, 2023)

Independent and combined effects of exposure to organophosphate esters on thyroid hormones in children and adolescents - Liqin Hu; Bin Zhou; Yaping Li; Lulu Song; Jin Wang; Meng Yu; Xiang Li; Ling Liu; Jing Kou; Youjie Wang; Xijiang Hu; Surong Mei (Environmental Geochemistry and Health, 2023)

The association between organophosphate esters exposure and body mass index in children and adolescents: The mediating effect of sex hormones - Yaping Li; Liqin Hu; Bin Zhou; Zhiyi Zheng; Qitong Xu; Jun Liu; Lulu Song; Youjie Wang; Surong Mei (Chemosphere, 2023)

Elevated CO2 and temperature increase arbuscular mycorrhizal fungal diversity, but decrease root colonization, in maize and wheat - Zihao Liu; Zhenhua Yu; Bin Song; Yansheng Li; Jie Fang; Yaping Guo; Jian Jin; Jonathan M. Adams (Science of The Total Environment, 2023)

Association Analysis of 27 Single Nucleotide Polymorphisms in a Chinese Population with Essential Tremor - Lanxiao Cao; Luyan Gu; Jiali Pu; Dayao Lv; Jun Tian; Xinzhen Yin; Ting Gao; Zhe Song; Jinyu Lu; Gaohua Zhao; Baorong Zhang; Yaping Yan; et al. (Journal of Molecular Neuroscience, 2023)

Angelica sinensis polysaccharides prevents hematopoietic regression in D-Galactose-Induced aging model via attenuation of oxidative stress in hematopoietic microenvironment - Pengwei Jing; Xiaoying Song; Lirong Xiong; Biyao Wang; Yaping Wang; Lu Wang (Molecular Biology Reports, 2023)

Higher pH is associated with enhanced co‐occurrence network complexity, stability and nutrient cycling functions in the rice rhizosphere microbiome - Yaping Guo; Bin Song; Anqi Li; Qi Wu; Haili Huang; Na Li; Ying Yang; Jonathan Miles Adams; Lin Yang (Environmental Microbiology, 2022)
The rice rhizosphere microbiota is crucial for crop yields and nutrient use efficiency. However, little is known about how co‐occurrence patterns, keystone taxa and functional gene assemblages relate to soil pH in the rice rhizosphere soils. Using shotgun metagenome analysis, the rice rhizosphere microbiome was investigated across 28 rice fields in east‐central China. At higher pH sites, the taxonomic co‐occurrence network of rhizosphere soils was more complex and compact, as defined by higher average degree, graph density and complexity. Network stability was greatest at medium pH (6.5

Correction to: Alpinia officinarum mediated copper oxide nanoparticles: synthesis and its antifungal activity against Colletotrichum gloeosporioides - Chunmei Hu; Wenjia Zhu; Ying Lu; Yanfang Ren; Jinyu Gu; Yaping Song; Junyu He (Environmental Science and Pollution Research, 2022)

Alpinia officinarum mediated copper oxide nanoparticles: synthesis and its antifungal activity against Colletotrichum gloeosporioides - Chunmei Hu; Wenjia Zhu; Ying Lu; Yanfang Ren; Jinyu Gu; Yaping Song; Junyu He (Environmental Science and Pollution Research, 2022)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Construction of WO3 nanocubes@Loess for rapid photocatalytic degradation of organics in wastewater under sunlight - Hua Yang; Peiyu Cao; Yaping Zhang; Meiling Zhou; Qianqian Wang; Rongmin Wang; Pengfei Song; Yufeng He (Environmental Science and Pollution Research, 2022)

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

Organophosphate esters in children and adolescents in Liuzhou city, China: concentrations, exposure assessment, and predictors - Meng Yu; Xiang Li; Bingqing Liu; Yaping Li; Ling Liu; Limei Wang; Lulu Song; Youjie Wang; Liqin Hu; Surong Mei (Environmental Science and Pollution Research, 2022)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Exosomes derived from astrocytes after oxygen-glucose deprivation promote differentiation and migration of oligodendrocyte precursor cells in vitro - Yaping Xu; Yeye Tian; Yao Wang; Li Xu; Guini Song; Qiao Wu; Wei Wang; Minjie Xie (Molecular Biology Reports, 2021)

Decreased grain size1, a C3HC4-type RING protein, influences grain size in rice (Oryza sativa L.) - Xingjie Zhu; Shengzhong Zhang; Yaping Chen; Changlin Mou; Yunshuai Huang; Xi Liu; Jingli Ji; Jiangfeng Yu; Qixian Hao; Chunyan Yang; Mengying Cai; Thanhliem Nguyen; et al. (Plant Molecular Biology, 2021)

Sediment transport under increasing anthropogenic stress: Regime shifts within the Yellow River, China - Shuang Song; Shuai Wang; Bojie Fu; Yanxu Liu; Kevin Wang; Yikai Li; Yaping Wang (Ambio, 2020)

Could urinary ACE2 protein level help identify individuals susceptible to SARS-CoV-2 infection and complication? - Xiaotian Ni; Changqing Sun; Yaping Tian; Yanjie Huang; Tongqing Gong; Lan Song; Xing Yang; Kai Li; Nairen Zheng; Jianping Wang; Hongxing Wu; Ruoxian Zhang; et al. (Science China Life Sciences, 2020)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Gene UCHL1 expresses specifically in mouse uterine decidual cells in response to estrogen - Lishuang Hao; Di Song; Mengfei Zhuang; Yan Shi; Lin Yu; Yaping He; Jian Wang; Tingting Zhang; Zhaogui Sun (Histochemistry and Cell Biology, 2020)

Genetic Structure and Diversity of Glycyrrhiza Populations Based on Transcriptome SSR Markers - Yaling Liu; Yaping Geng; Meiling Song; Pengfei Zhang; Junling Hou; Wenquan Wang (Plant Molecular Biology Reporter, 2019)

Design and Development of Lidocaine Microemulsions for Transdermal Delivery - Yaping Wang; Xihui Wang; Xiangyu Wang; Yilei Song; Xiaodan Wang; Jifu Hao (AAPS PharmSciTech, 2019)

Correlation of IL-31 gene polymorphisms with susceptibility and clinical recurrence of bladder cancer - Qin Li; Tielong Tang; Peng Zhang; Chenlu Liu; Yan Pu; Yan Zhang; Huizi Song; Yanyun Wang; Yaping Song; Min Su; Bin Zhou; Lin Zhang (Familial Cancer, 2018)

Association of genetic variations in RTN4 3′-UTR with risk for clear cell renal cell carcinoma - Yan Pu; Peng Chen; Bin Zhou; Peng Zhang; Yanyun Wang; Yaping Song; Lin Zhang (Familial Cancer, 2018)

Neuroprotective Effect of Osthole on Neuron Synapses in an Alzheimer’s Disease Cell Model via Upregulation of MicroRNA-9 - Shaoheng Li; Yuhui Yan; Yanan Jiao; Zhong Gao; Yang Xia; Liang Kong; Yingjia Yao; Zhenyu Tao; Jie Song; Yaping Yan; Guangxian Zhang; Jingxian Yang (Journal of Molecular Neuroscience, 2016)

ace-3 plays an important role in phoxim resistance in Caenorhabditis elegans - Yan Han; Shaojuan Song; Yaping Guo; Jianzhen Zhang; Enbo Ma (Ecotoxicology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Removal of Trace As(V) from Water with the Titanium Dioxide/ACF Composite Electrode - Liang Peng; Yaping Chen; Hong Dong; Qingru Zeng; Huijuan Song; Liyuan Chai; Ji-dong Gu (Water, Air, & Soil Pollution, 2015)

Single nucleotide polymorphisms in PDCD6 gene are associated with the development of cervical squamous cell carcinoma - Bin Zhou; Peng Bai; Hui Xue; Zhu Zhang; Shaoqing Shi; Kui Zhang; Yanyun Wang; Kana Wang; Yi Quan; Yaping Song; Lin Zhang (Familial Cancer, 2015)

Trends of subtype variation of human immunodeficiency virus type 1 in Zhejiang Province, China - Yaping Yao; Ruolei Xin; Jiezhe Yang; Yun Xu; Jiafeng Zhang; Yan Xia; Xiaohong Pan; Zhihong Guo; Yanhui Song (Virus Genes, 2015)

Removal of trace Cd(II) from water with the manganese oxides/ACF composite electrode - Yaping Chen; Liang Peng; Qingru Zeng; Yang Yang; Ming Lei; Huijuan Song; Liyuan Chai; Jidong Gu (Clean Technologies and Environmental Policy, 2015)

A polymorphism at miRNA-122-binding site in the IL-1α 3′UTR is associated with risk of epithelial ovarian cancer - Zhu Zhang; Bin Zhou; Qianqian Gao; Yuke Wu; Kui Zhang; Yan Pu; Yaping Song; Lin Zhang; Mingrong Xi (Familial Cancer, 2014)

Expression and functional analysis of a glycoside hydrolase family 45 endoglucanase from Rhizopus stolonifer - Bin Tang; Yingying Zhang; Yaping Yang; Zhewei Song; Xianglin Li (World Journal of Microbiology and Biotechnology, 2014)

Changes to Cuticle Surface Ultrastructure and Some Biological Functions in the Nematode Caenorhabditis Elegans Exposed to Excessive Copper - Shaojuan Song; Yaping Guo; Xiaomin Zhang; Xueyao Zhang; Jianzhen Zhang; Enbo Ma (Archives of Environmental Contamination and Toxicology, 2014)

Prognostic value of IL-27 polymorphisms and the susceptibility to epithelial ovarian cancer in a Chinese population - Zhu Zhang; Bin Zhou; Yuke Wu; Qianqian Gao; Kui Zhang; Yaping Song; Lin Zhang; Mingrong Xi (Immunogenetics, 2014)

The influence of vegetation variation on Northeast Asian dust activity - Rui Mao; Chang-Hoi Ho; Song Feng; Dao-Yi Gong; Yaping Shao (Asia-Pacific Journal of Atmospheric Sciences, 2013)

Association between polymorphisms in the signal transducer and activator of transcription and dilated cardiomyopathy in the Chinese Han population - Ying Peng; Bin Zhou; Yanyun Wang; Yu Chen; Hui Li; Yaping Song; Lin Zhang; Li Rao (Molecular and Cellular Biochemistry, 2012)

Distribution of borehole temperature at four high-altitude alpine glaciers in Central Asia - Yaping Liu; Shugui Hou; Yetang Wang; Linlin Song (Journal of Mountain Science, 2009)

The Polymorphism of DNA Repair Gene ERCC2/XPD Arg156Arg and Susceptibility to Breast Cancer in a Chinese Population - Jiaoyang Yin; Duohong Liang; Ulla Vogel; Yaping Chang; Zhengrong Liu; Li Yue; Xiaoling Sun; Rong Qi; Tiehua Song (Biochemical Genetics, 2009)

Lack of mtDNA control region variation in Hainan Eld's deer: Consequence of a recent population bottleneck? - Junfeng Pang; A. Rus Hoelzel; Yanling Song; Zhigao Zeng; Yaping Zhang (Conservation Genetics, 2003)